Path Dependency, Demographic Change, and the (De-)Differentiation of the German Secondary School System - Bartl, Walter [Verfasser]; Sackmann, Reinhold [Verfasser] (My University, 2014)
"Current sociological debate on the effects of demographic chance on education systems still swings between the ectremes of 'demography as ideology', which conseives of demographic change as a phemomenon with immediate impact, and 'demography as ideology', which questions any relvance of demographic factors at all. This article adops a Durckheimian perspective and checks whether changes in the division of labor moderate the effects of demographic change. This hypothesis is testing by analyzing panel data at the regional level of counties on the differentiation of the German Secondary school system for the years 1995-2010. In addition to demography, the effects of path dependency, party politics, and German re-unification are modeled as well. The analysis shows a moderate effect of demogaphic change on the (de-)differentiation of the German secondary school system." (Autorenreferat, BIBB-Doku)

"Der soziologische Diskurs über die Folgen des demographischen Wandels für Bildungssysteme schwankt immer noch zwischen den Extremen "Demographie als Schicksal“, was Bevölkerungsveränderungen unmittelbare Folgen zuschreibt, und "Demographie als Ideologie“, was die Relevanz demographischer Faktoren grundsätzlich in Frage stellt. Der vorliegende Aufsatz nimmt eine Durkheim’sche Perspektive ein und prüft, ob Veränderungen der Arbeitsteilung die Folgen des demographischen Wandels moderieren. Diese Hypothese wird mit Hilfe von Paneldaten über die Differenzierung des deutschen Sekundarschulsystems auf der regionalen Ebene der Kreise für die Jahre 1995-2010 analysiert. Zusätzlich zu demographischen Veränderungen werden auch Effekte von Pfadabhängigkeit, Parteiideologie und der Wiedervereinigung modelliert. Die Analyse zeigt einen moderaten Effekt des demographischen Wandels auf die (Ent-)Differenzierung des deutschen Sekundarschulsystems." (Autorenreferat, BIBB-Doku)
Keywords: G 1.1.1 Demografie; S 1.1 Allgemeinbildende Schule; Demografischer Wandel; Arbeitsteilung; Differenzierung; Schulwesen; Sekundarbereich